Sources of versions during a murders investigation - Семеногов, В. В. (Theory and practice of jurisprudence, 2016)
The concept of «version» and its role in an investigation had been analyzed. The problems of constructing versions during investigation of murders had been highlighted. The classification of sources that can be used for the construction of investigative leads had been examined.